1988
DOI: 10.3109/01050398809070699
|View full text |Cite
|
Sign up to set email alerts
|

Contralateral Routing of Signals in Unilateral Hearing ImpairmentA Better Method of Fitting

Abstract: Unilaterally severely hearing impaired persons, who may experience substantial communication problems in situations of high acoustic demands, would in theory benefit from contralateral routing of signals (CROS). However, reports of failure because of too much disturbing noise and distortion have been common. The reason for a low success rate in CROS, though, is an inappropriate fitting procedure, due to lack of understanding of the basic principle of CROS among both patients and audiologists. The precondition … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 8 publications
0
11
0
Order By: Relevance
“…Early reports of benefit in monaural listeners with CROS hearing devices suggested that lifting of the head-shadow resulted in significant benefit to this population (13). However, this treatment was plagued by acoustic limitations that resulted in complaints of poor sound quality and discomfort with device use (12,13) ultimately leading to a lack of acceptance for CROS as a treatment solution by individuals with unilateral severe-profound sensorineural hearing loss.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Early reports of benefit in monaural listeners with CROS hearing devices suggested that lifting of the head-shadow resulted in significant benefit to this population (13). However, this treatment was plagued by acoustic limitations that resulted in complaints of poor sound quality and discomfort with device use (12,13) ultimately leading to a lack of acceptance for CROS as a treatment solution by individuals with unilateral severe-profound sensorineural hearing loss.…”
Section: Discussionmentioning
confidence: 99%
“…The CROS hearing aid was first introduced by Harford and Barry (11) in 1965. Poor acceptance of CROS hearing aids at this time are largely attributed to complaints of occlusion in the better ear, poor sound quality, and discomfort (12,13). Additional limitations included aesthetics, size, and poor battery life.…”
Section: Introductionmentioning
confidence: 99%
“…Early reports of benefit in monaural listeners with CROS hearing devices suggested that lifting of the head-shadow resulted in significant benefit to this population 14 . However, the acoustic limitations of early CROS systems resulted in complaints of poor sound quality and discomfort with device use 13,14 .…”
Section: Discussionmentioning
confidence: 99%
“…However, the acoustic limitations of early CROS systems resulted in complaints of poor sound quality and discomfort with device use 13,14 . Some have attributed poor acceptance of CROS technology to the inability to restore binaural function 11 as rerouting the signal to the normal hearing ear does not provide distinct binaural processing for advanced auditory processing abilities such as localization.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation